Identification of QTLs for cadmium tolerance during seedling stage and validation of qCDSL1 in rice - Shilin, Ding; Chaolei, Liu; Lianguang, Shang; Shenglong, Yang; Anpeng, Zhang; Hongzhen, Jiang; Banpu, Ruan; Guonan, Fang; Biao, Tian; Ye, Guoyou; Guo, Longbiao; Qian, Qian; et al. (Elsevier, 2021)
Cadmium (Cd) is a non-essential toxic metal that is harmful to plants. To investigate the genetic mechanism of Cd tolerance in rice, quantitative trait loci (QTLs) associated with Cd tolerance at the seedling stage were analyzed using a recombinant inbred line (RIL) population derived from a cross between PA64s and 93-11. A total of 36 QTLs associated with shoot length, root length, shoot dry weight, root dry weight and total dry weight were detected in Hangzhou and Lingshui of China. Among them, 15 QTLs were identified under the control condition and 15 QTLs were identified under the Cd stress condition, and 6 QTLs for Cd tolerant coefficient were detected on chromosomes 1, 3, 7 and 9. The qCDSL1.1 and qCDSL1.2 were identified in Hangzhou and Lingshui, respectively, and had overlapping intervals on chromosome 1. To further confirm the effects of qCDSL1.1 and qCDSL1.2, we developed a chromosome segment substitution line (CSSL), CSSLqCDSL1, in 93-11 background harboring qCDSL1.1/qCDSL1.2 from PA64s. Compared to 93-11, CSSLqCDSL1 had increased shoot length under the Cd stress condition. These results pave the way for further isolation of those genes controlling Cd tolerance in rice and marker-assistant selection of rice elite varieties with Cd tolerance.